Quantitative Easing and Long-Term Yields in Small Open Economies - Diez de los Rios, Antonio (IMF Working Papers; Working Paper ;, 2017)
We compare the effectiveness of Federal Reserve's asset purchase programs in lowering longterm yields with that of similar programs implemented by the Bank of England, the Swedish Riksbank, and the Swiss National Bank's reserve expansion program. We decompose government bond yields into (i) an expectations component, (ii) a global, and (iii) a country specific term premium to analyze two-day changes in 10-year yields around announcement dates. We find that, in contrast to the Federal Reserve's asset purchases, the programs implemented in these smaller economies have not been able to affect the global term premium and, furthermore, they have had limited, but significant, effect in lowering long-term yields.